New species of Neuronema McLachlan, 1869 from China (Neuroptera, Hemerobiidae) - Zhao, Yang; Yan, Bingzhen; Liu, Zhiqi (Zootaxa, 2013)
Two new species of Neuronema McLachlan are described from China: Neuronema ypsilum sp. nov., which was found in Beijing and Shaanxi provinces, and Neuronema maculosum sp. nov., which was found in Chongqing and Gansu provinces. Keys are given to identify the species of Neuronema in China.